Observations about Anacreon, PMG 395 (Circe de clásicos y modernos, 2018)
The goal of this paper is to conduct a rhythmical-melodical analysis of Anacreon’s PMG 395. After a presentation of the text, including a study of the main discussions about it in scholarship, the author analyzes it by studying the distribution of enjambments and accents in the lines. Finally, he suggests that the conclusions obtained have a scope that is not limited to PMG 395 in particular, but that they improve our understanding of the poetic technique of Anacreon in general.
Keywords: Anacreon; PMG 395; Anacreontic; Ancient Greek Metric; Ancient Greek Music